Audio Visual Teaching Materials Based on Flash to Train Students Skill to Create Mind Mapping in Simple Harmonic Motion - Reni Puspitasari; Yetti Supriyati; Dwi Susanti (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2020)
Abstract. The purpose of this study is to develop audio visual teaching materials based on flash that can makes students enable to rewrite every recovered material in the form of mind mapping on simple harmonic motion materials. The concept of teaching materials development is based on basic revision competence of the 2013 curriculum in x class. This study uses the method of research and development (RND) with an ADDIE development model. This ADDIE development models have five stages, the analytic stages (Analytic), the development stages (Development), the implementation (Implementation), and the evaluating stage (Evaluation). The product produced in the form of flash-based audio visual teaching material that can be used to support learning activities by teachers and independent teaching materials for students to practice skills in making mind mapping easily. Assessments of the product are made by materials experts, media experts, and learning professionals. Prodik trials are conducted on high school physics teachers and high school students.